PENGARUH KARAKTERISTIK KOMITE AUDIT DAN AUDITOR EKSTERNAL TERHADAP KUALITAS LABA (STUDI BANK-BANK SHARIA DI ASIA TENGGARA) - Warsito Kawedar; Fitrarena Widhi Rizkyana; Rr. Sri Handayani (Jurnal Akuntansi, 2021)
This study aimed to analyze the influence of audit committee characteristics (size, independence, expertise, the former audit partner, and gender diversity) on quality of earnings. External auditor roles as moderating variable. This research was conducted at Islamic banks in Southeast Asia in the period 2012-2017. There were 152 samples in this study obtained through purposive sampling technique. The analysis technique used to test hypotheses is the absolute difference value model. The results of this study found evidence that the size of the audit committee, the independence of the audit committee, and the former audit partner has a positive influence on earnings quality. The audit committee's expertise does not have an effect on earnings quality, and the audit committee's gender diversity has a negative influence on earnings quality. Meanwhile, the external auditor only moderates the relationship between gender diversity committee audit on the quality of earnings.